Looking for Motivation? Understanding the Effects of Amotivation in a Multigenerational Workforce - Blasa-Cheng, Angelique C.; Ang, Danika Therese R.; Locsin, Luis Alfonso R.; Laguitan, Angeline Beatrice G.; Rodriguez, Jeanelle M.; Mabalay, Adrian A.; Vergara, Raymond Allan G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Using a sequential explanatory mixed-methods approach, the study investigated the impact of job design on amotivation, job engagement, time commitment, and work intensity among Generation Y and Z employees in the Philippine e-commerce industry.  The study revealed that job design has a significant influence on amotivation and job engagement, with autonomy and competence emerging as critical factors. Relatedness, however, had minimal impact. The study also finds that job engagement fully mediates the relationship between job design and work intensity. These findings contribute to the theoretical understanding of amotivation in the workplace by identifying key job design elements that affect it and its consequent impact on employee behaviors. The findings also guide organizations in designing jobs that optimize motivation and engagement for Generation Y and Z employees.